Knock-in mice harboring a Ca2+ desensitizing mutation in cardiac troponin C develop early onset dilated cardiomyopathy - McConnell, Bradley K.; Singh, Sonal; Fan, Qiying; Hernandez, Adriana; Portillo, Jesus P.; Reiser, Peter J.; Tikunova, Svetlana (Frontiers in Physiology, 2015)
The physiological consequences of aberrant Ca2+ binding and exchange with cardiac myofilaments are not clearly understood. In order to examine the effect of decreasing Ca2+ sensitivity of cTnC on cardiac function, we generated knock-in mice carrying a D73N mutation (not known to be associated with heart disease in human patients) in cTnC. The D73N mutation was engineered into the regulatory N-domain of cTnC in order to reduce Ca2+ sensitivity of reconstituted thin filaments by increasing the rate of Ca2+ dissociation. In addition, the D73N mutation drastically blunted the extent of Ca2+ desensitization of reconstituted thin filaments induced by cTnI pseudo-phosphorylation. Compared to wild-type mice, heterozygous knock-in mice carrying the D73N mutation exhibited a substantially decreased Ca2+ sensitivity of force development in skinned ventricular trabeculae. Kaplan-Meier survival analysis revealed that median survival time for knock-in mice was twelve weeks. Echocardiographic analysis revealed that knock-in mice exhibited increased left ventricular dimensions with thinner walls. Echocardiographic analysis also revealed that measures of systolic function, such as ejection fraction and fractional shortening, were dramatically reduced in knock-in mice. In addition, knock-in mice displayed electrophysiological abnormalities, namely prolonged QRS and QT intervals. Furthermore, ventricular myocytes isolated from knock-in mice did not respond to β-adrenergic stimulation. Thus, knock-in mice developed pathological features similar to those observed in human patients with dilated cardiomyopathy (DCM). In conclusion, our results suggest that decreasing Ca2+ sensitivity of the regulatory N-domain of cTnC is sufficient to trigger the development of DCM.